2015
DOI: 10.1016/j.proeng.2015.06.081
|View full text |Cite
|
Sign up to set email alerts
|

A Raspberry in Sub-Saharan Africa? Chances and Challenges of Raspberry Pi and Sensor Networking in Humanitarian Logistics

Abstract: This paper addresses the chances and challenges of humanitarian logistics in Sub-Saharan Africa with a special view on the application of single-board computers -such as the Raspberry Pi -in combination with sensor networking. In this connection the paper deals with the following questions: Which special circumstances in and challenges for Sub-Saharan Africa need to be considered? How can humanitarian logistics contribute to enhance the supply of people in need with food and medicines? Are Raspberry Pi or othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Ahmadi et al considered the network failure, multiple uses of vehicles and standard relief time in a multi-depot location-routing model, and the results demonstrated that the unsatis?ed demands could be signi?cantly reduced at the cost of higher number of local depots and vehicles [7]. Schumann-Bolsche et al, in a special view, combined single-board computers -such as the Raspberry P i -and sensor networking to study the chances and challenges of humanitarian logistics in Sub-Saharan Africa [8]. Scarpin et al identified the critical factors that help logistics processes in cases of environmental disasters based on a case study that corroborates the Balcik theoretic model, and the results manifested that all links (among suppliers, donors, beneficiaries and distribution center) in the chain manifested post-disaster [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ahmadi et al considered the network failure, multiple uses of vehicles and standard relief time in a multi-depot location-routing model, and the results demonstrated that the unsatis?ed demands could be signi?cantly reduced at the cost of higher number of local depots and vehicles [7]. Schumann-Bolsche et al, in a special view, combined single-board computers -such as the Raspberry P i -and sensor networking to study the chances and challenges of humanitarian logistics in Sub-Saharan Africa [8]. Scarpin et al identified the critical factors that help logistics processes in cases of environmental disasters based on a case study that corroborates the Balcik theoretic model, and the results manifested that all links (among suppliers, donors, beneficiaries and distribution center) in the chain manifested post-disaster [9].…”
Section: Literature Reviewmentioning
confidence: 99%